Design and Development of Rent Anything Web-based System for UTHM Community - Ahmad Shukry, Aina Saffiya; Wahid, Norfaradilla (Applied Information Technology And Computer Science, 2025)
Rent-Anything is a web-based system specifically for the UTHM community at both Parit Raja and Pagoh campuses which proposed to manage all rental activities within the UTHM community such as registration, the listing process, and as well as the renting process. The unavailability of a platform to list items for rent led to the development of a more streamlined system that simplifies the rental process, improves usability, and features a better graphical user interface (GUI). Incorporating such features would make the system more effective, user-friendly, and accessible, improving the overall experience for users and facilitating smoother transactions. The project is developed based on the Prototype Model methodology. As for the implementation, the system is implemented using HTML, CSS, PHP, and SQL as the database. At the end of the project, the Rent-Anything system successfully delivered a seamless and functional platform that enabled the UTHM community at both Parit Raja and Pagoh campuses to manage rental activities efficiently. System testing validated its effectiveness, confirming that the platform met user needs and offered a user-friendly experience.